Factores de riesgo que inciden en la prevalencia de las parasitosis intestinales en niños de 5 a 12 años. Unidad Educativa Luis Aurelio González, Cantón San Miguel, período mayo-agosto 2024. - Illachuma Chimbo, Evelyn Lizeth (2024)
Introduction: intestinal parasitosis is characterized by the presence and development of parasites within the gastrointestinal tract. These infections mainly affect children and are generally related to different factors. Objective: to determine the risk factors that affect the prevalence of intestinal parasitosis in children from 5 to 12 years old who attend the Luis Aurelio González Educational Unit of San Miguel canton, San Vicente parish, Bolivar province, during the period May-August 2024. Methodology: a descriptive, non-experimental field study was carried out, with a quantitative-qualitative approach. The study population consisted of 20 minors. A Likert scale questionnaire was used, addressed to the children's parents or guardians. Results: there was a prevalence of intestinal parasitosis in 45 % of the children. Eighty.0% of the parents or guardians lacked knowledge about these infections. Regarding hygiene practices, 50% of the children wash their hands before eating, and 70% after defecating. Seventy percent of the families dispose of their waste in septic tanks and 45.0% receive annual deworming. 45.0% of the children interact daily with domestic animals. Regarding infrastructure, 50.0% consider the hygiene of the community to be adequate and 60.0% consider the hygiene of the educational unit to be adequate. Conclusion: the most prevalent risk factors include socioeconomic, education the health and infrastructure aspects; therefore, it is necessary to implement prevention strategies through educational programs and continuous health controls.